The Development of "HOTS" Assessment Instruments in Enhanced Students' Understanding of Elementary School Science Subjects - Widia Indah Rahayu; Yuyu Yuhana; Ratna Sari Dewi (Jurnal Penelitian Pendidikan IPA, 2023)
Education is a learning process that enables the younger generation to live their lives more effectively and efficiently. Teacher are one of the purpose of the learning process. Teachers who do learning in a class using a model or a varying learning method will develop abilities and skills. The research was intended for the development of test assessments in the form of hots at the elementary school for the fourth grade. The "r&d" study method used. Research development with a four (4D) model of 4 degrees define, design, development and disseminate. The methods of data collection used to validate the development of instruments to assess students' understanding of the scientific topic of nature are a component of research development. Based on data analysis of the validation team experts in Numbers form, the evaluating stage is scaled at 94%, making a 92% conclusion, integrating 94%, identifying 91%, and on the explaining aspect is obtained 89%. The results of test instruments include cognition with an 85% percentage, a 95% afscreening aspect and a 90% psychomotor aspect. Activate the test tools of the "very good" instruments that enable it in the student's understanding at school